Are digital social media campaigns the key to raise stroke awareness in low-and middle-income countries?: a study of feasibility and cost-effectiveness in Nepal - Tunkl, Christine; Paudel, Raju; Thapa, Lekhjung; Tunkl, Patrick; Jalan, Pankaj; Chandra, Avinash; Belson, Sarah; Prasad Gajurel, Bikram; Haji Begli, Nima; Bajaj, Sunanjay; Golenia, Jessica; Wick, Wolfgang; et al. (PLOS ONE, 2023)
BACKGROUND: Stroke is a major global health problem and was the second leading cause of death worldwide in 2020. However, the lack of public stroke awareness especially in low- and middle-income countries (LMICs) such as Nepal severely hinders the effective provision of stroke care. Efficient and cost-effective strategies to raise stroke awareness in LMICs are still lacking. This study aims to (a) explore the feasibility of a social media-based stroke awareness campaign in Nepal using a cost-benefit analysis and (b) identify best practices for social media health education campaigns. METHODS: We performed a stroke awareness campaign over a period of 6 months as part of a Stroke Project in Nepal on four social media platforms (Facebook, Instagram, Twitter, TikTok) with organic traffic and paid advertisements. Adapted material based on the World Stroke Day Campaign and specifically created videos for TikTok were used. Performance of the campaign was analyzed with established quantitative social media metrics (impressions, reach, engagement, costs). RESULTS: Campaign posts were displayed 7.5 million times to users in Nepal. 2.5 million individual social media users in Nepal were exposed to the campaign on average three times, which equals 8.6% of Nepal's total population. Of those, 250,000 users actively engaged with the posts. Paid advertisement on Facebook and Instagram proved to be more effective in terms of reach and cost than organic traffic. The total campaign cost was low with a "Cost to reach 1,000 users" of 0.24 EUR and a "Cost Per Click" of 0.01 EUR. DISCUSSION: Social media-based campaigns using paid advertisement provide a feasible and, compared to classical mass medias, a very cost-effective approach to inform large parts of the population about stroke awareness in LMICs. Future research needs to further analyze the impact of social media campaigns on stroke knowledge.
Gesehen am 12.02.2024